Laboratory study and mathematical modeling of a novel marsh shoreline protection technology for sand collection. (July 2018) - Sakib, Salman; Gang, Daniel; Besse, Grant; Tang, Bao-bao; McCoy, Nicholas; Hayes, Donald
Highlights: Sand collection efficiency of the Wave Suppressor and Sediment Collection (WSSC) system was explored. WSSC system collected sands at 0.24 (kg/h) for Sand 1 and 0.36 (kg/h) for Sand 2 with an average efficiency of 63%. A new mathematical model was developed and it fit the sand collection data reasonably well. Water depth, wave height, and particle diameter were identified as the most important factors affecting sand collection. Abstract: Erosion along shorelines is a major cause in the conversion of shoreline wetlands to open water bodies. Conventional shoreline protection structures are expensive to construct and may impede environmental exchanges essential for connectivity and functionality. A novel marsh shoreline protection technology, the Wave Suppressor and Sediment Collection (WSSC) system, addresses these issues. Laboratory studies were conducted on three WSSC units to determine the governing parameters of sediment collection efficiency of this technology. The three units had varying open areas and pipe sizes which enabled those parameters to be directly compared. Two types of sands with median particle diameters ( d50 ) of 0.43 and 0.34 mm were used to evaluate the effects of particle size on the collection efficiency of the units. A new mathematical model was developed to predict the sediment collection efficiency using Van Rijn's equation for particle fall velocity, and Ribberink and Al-Salem's equation for sand concentration distribution in a water column. Results showed that the Unit 1, Unit 2 and Unit 3 are capable of collecting sand at 0.30, 0.21 and 0.21 (kg/h) for sand 1, and at 0.39, 0.29, 0.39 (kg/h) for sand 2 respectively. The mathematical model fit the experimental data well and from the model, mass accumulation coefficient (α) alpha was calculated. Mass accumulation coefficients (α) for sand 1 and sand 2 were- 0.94 and 0.97 for Unit 1, 0.63 and 0.70 for Unit 2 and 0.32 and 0.22 for Unit 3 respectively. A sensitivity study of the mathematical model was also performed to determine the governing factors behind the sand collection. The sensitivity study found that water depth, wave height and particle diameter affected the sand collection efficiency the most. The amount of open area on the units, frequency and wavelength were also found to have some effect on collection efficiency.